Option pricing in Heston model by means of weak approximations - Lenkšas, Antanas; Mackevičius, Vigirdas (Lietuvos matematikos rinkinys, 2013)
We apply weak split-step approximations of the Heston model for evaluation of put and call option prices in this model.